Community-based housing solutions in Hong Kong: how and why have they emerged?. Issue 2 (2nd April 2020) - Lau, Mandy
Abstract: This paper reviews the emergence of community-based housing solutions in Hong Kong, including the Community Housing Movement (CHM) which was formally launched in late 2017. This phenomenon shares some of the features of community-based housing solutions in other places, such as collaboration between government, market and civil society actors to tackle housing undersupply problems. Nevertheless, there are some locally distinctive drivers behind this phenomenon. On one hand, community housing projects have been catalysed by the plight of low-income immigrant households in the private rental market, who live in poor-quality sub-divided flats. On the other hand, these projects were initiated by a local philanthropist, before being institutionalised by community organisations and attracting financial support from the government. The review concludes by emphasising the importance of going beyond the rhetoric of community housing and focusing on the root causes of affordability problems, since lower-middle income households are unlikely to benefit from current forms of community housing solutions, yet struggle with the lack of affordable homeownership opportunities in a neoliberal housing market.